"Hope crept in": a phenomenological study of mentally ill artists' biographic narrative. (April 2015) - Sagan, Olivia
Abstract Background: The ways in which involvement in art practice may support a recovery trajectory in the lives of the mentally ill are well documented although evidence is charged with lacking clarity and of being inconclusive. Numerous studies, however, indicate benefits such as cognitive distraction; "derailing" of negative thinking patterns; increased social capital; and enhanced sense of belonging. Aims: This study used narrative interviews to explore what meanings were made by people with mental health difficulties of engaging in an ongoing visual art practice. Methods: Phenomenological Interpretative Analysis (IPA) was used to analyse 50 interviews. Two superordinate themes of regression and progression were identified through which to explore the shifts in narrative between exploring one's past and looking ahead to the future. In this context, the theme of hope emerged, and the research explored the ways in which the individual's art practice was implicated in engendering and sustaining it. Results: Results suggest that artistic activity facilitated a contained autobiographical analysis and a reimagining of oneself in the future, in which hope played a fundamental part. Conclusion: This research suggests that a dialectic between despair and hope is facilitated by the autobiographic elements of an art practice. Through this movement from a perceived static past to a more fluid future is experienced.